(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
This thesis aims to research the value and influence of digital marketing on the competitive establishment of startup companies. The research would further explore whether digital marketing can substantially affect the growth of startups, enhance brand recognition, gain consumer loyalty, and strengthen customer relationships. This concept has yet to be previously researched. The only related Study we found was the correlation between social media and innovation in startups, which indicates that social media positively affects innovation in startup companies. The research used a qualitative approach in which five startup firms were interviewed using a semi-structured interview as the primary data collection method. The research also collected secondary data from peer-reviewed articles, journals, and websites. The Study concludes that digital marketing is recognised as a creative and efficient way of obtaining, sustaining, and establishing customer relationships. Online channels and platforms, such as websites, industry-specific outlets, and forums, have been identified to be the most beneficial for startups. It also suggests that a fresh startup can develop substantially through digital marketing by creating brand awareness, building trust, and building consumer awareness. However, most startup companies hesitate to implement digital marketing strategies at the beginning of the company's establishment. Our findings will assist other startups in considering digital marketing for their marketing strategies. Recommendations for further studies are a related but more detailed study in Madhya Pradesh and a study in a central state of the country.